A Very Long Baseline Interferometry Calibrator Grid at 600 MHz for Fast Radio Transient Localizations with CHIME/FRB Outriggers - Shion Andrew; Calvin Leung; Alexander Li; Kiyoshi W. Masui; Bridget C. Andersen; Kevin Bandura; Alice P. Curtin; Jane Kaczmarek; Adam E. Lanman; Mattias Lazda; Juan Mena-Parra; Daniele Michilli; et al. (The Astrophysical Journal)
The Canadian Hydrogen Intensity Mapping Experiment Fast Radio Burst (CHIME/FRB) Project has a new very long baseline interferometry (VLBI) Outrigger at the Green Bank Observatory (GBO), which forms a 3300 km baseline with CHIME operating at 400–800 MHz. Using 100 ms long full-array baseband “snapshots” collected commensally during FRB and pulsar triggers, we perform a shallow, wide-area VLBI survey covering a significant fraction of the northern sky targeted at the positions of compact sources from the Radio Fundamental Catalog. In addition, our survey contains calibrators detected from two 1 s long trial baseband snapshots for a deeper survey with CHIME and GBO. In this paper, we present the largest catalogue of compact calibrators suitable for 30 mas scale VLBI observations at subgigahertz frequencies to date. Our catalogue consists of 200 total calibrators in the Northern Hemisphere that are compact on 30 mas scales with fluxes above 100 mJy. This calibrator grid will enable the precise localization of hundreds of FRBs a year with CHIME/FRB Outriggers.